Design of a Circularly-Polarized Microstrip Antenna by Utilizing Mutually-Coupled Resonators - Jia-Xiang Hao; Hui-Dong Li; Lei Zhu (IEEE Open Journal of Antennas and Propagation)
This article proposes a design method for a circularly-polarized (CP) antenna, which is realized by using coupling effects. Initially, the desired electric(magnetic) coupling between two identical $λ$ /4 short-circuited microstrip line (MS-L) resonators can be generated when the short-circuited (opencircuited) ends of the resonators are in close proximity to each other. Besides, an orthogonal arrangement in space for these two resonators has been adopted to yield two orthogonal linearly-polarized (LP) waves. Therefore, a desired CP rotation can be achieved by choosing corresponding coupling types. Meanwhile, two equivalent circuit models are established and analyzed to deduce the formulas of the mutual inductance and mutual capacitance for the desired CP radiation. Afterwards, a binary array consisting of a magnetically coupled (MC) pair of resonators and an electrically coupled (EC) pair of resonators is proposed for expanding the axial ratio bandwidth (ARBW) and enhancing peak gain. Finally, a right-handed circularlypolarized (RHCP) antenna with magnetic coupling, a left-handed circularly-polarized (LHCP) antenna with electric coupling and a binary array are fabricated and tested. And an excellent agreement is validated between the experiment and simulation results. The measured results show that the binary array achieves a maximum gain of 5 dBic within its measured ARBW range of 3.535 – 3.615 GHz. In contrast, the single pairs (EC or MC pair) exhibit a gain of 3 dBic. Additionally, the array demonstrates a fivefold expansion in ARBW compared to the single pair.